Temporal patterns of Influenza A and B in tropical and temperate countries: what are the lessons for influenza vaccination? - Caini, Saverio (2016)
Authors - SAVERIO CAINI, affiliation Netherlands Institute for Health Services Research (NIVEL), Utrecht, The Netherlands; WINSTON ANDRADE, affiliation Sección de Virus Respiratorios y Exantemáticos, Instituto de Salud Pública de Chile, Santiago de Chile, Chile ; SELIM BADUR, affiliation Istanbul University, Istanbul, Turkey; ANGEL BALMASEDA, affiliation National Influenza Center, Ministry of Health, Managua, Nicaragua; AMAL BARAKAT, affiliation National Influenza Center, Institut National d'Hygiène, Ministry of Health, Rabat, Morocco; ANTONINO BELLA, affiliation National Center for Epidemiology, Surveillance and Health Promotion National Institute of Health, Rome, Italy; ABDERRAHMAN BIMOHUEN, affiliation National Influenza Center, Institut National d'Hygiène, Ministry of Health, Rabat, Morocco; LYNNETTE BRAMMER, affiliation Epidemiology and Prevention Branch, Influenza Division, Centers for Disease Control and Prevention, Atlanta, GA, United States of America; JOSEPH BRESEE, affiliation Epidemiology and Prevention Branch, Influenza Division, Centers for Disease Control and Prevention, Atlanta, GA, United States of America; ALFREDO BRUNO, affiliation Centro de Referencia Nacional de Influenza y Otros Virus Respiratorios, Instituto Nacional de Investigación en Salud Pública (INSPI), Guayaquil, Ecuador; LETICIA CASTILLO, affiliation National Influenza Center, Ministry of Health, Guatemala City, Guatemala; MERAL A. CIBLAK, affiliation Istanbul University, Istanbul, Turkey; ALEXEY W. CLARA, affiliation US Centers for Disease Control, Central American Region, Guatemala City, Guatemala; CHERYL COHEN, affiliations Centre for Respiratory Diseases and Meningitis (CRDM), National Institute for Communicable Diseases, Johannesburg, South Africa, School of Public Health, Faculty of Health Science, University of the Witwatersrand, Johannesburg, South Africa; JEFFERY CUTTER, affiliation Communicable Diseases Division, Ministry of Health, Singapore, Singapore; COULIBALY DAOUDA, affiliation Respiratory Viruses Unit, Pasteur Institute of Côte d’Ivoire, Abidjan, Côte d’Ivoire; CELINA DE LOZANO, affiliation National Influenza Center, Ministry of Health, San Salvador, El Salvador; DOMENICA DE MORA, affiliation Centro de Referencia Nacional de Influenza y Otros Virus Respiratorios, Instituto Nacional de Investigación en Salud Pública (INSPI), Guayaquil, Ecuador; KUNZANG DORJI, affiliation Public Health Laboratory, Department of Public Health, Ministry of Health, Thimphu, Bhutan; GIDEON O. EMUKULE, affiliation US Centers for Disease Control and Prevention, Nairobi, Kenya; RODRIGO A. FASCE, affiliation Sección de Virus Respiratorios y Exantemáticos, Instituto de Salud Pública de Chile, Santiago de Chile, Chile; LUZHAO FENG, affiliation Division of Infectious Disease, Key Laboratory of Surveillance and Early-warning on Infectious Disease, Chinese Center for Disease Control and Prevention, Beijing, China; WALQUIRIA APARECIDA FERREIRA DE ALMEIDA, affiliation Ministry of Health, Brasília, DF, Brazil; RAQUEL GUIOMAR, affiliation National Influenza Reference Laboratory, Infectious Diseases Department, National Institute of Health, Lisbon, Portugal; JEAN-MICHEL HERAUD, affiliation National Influenza Center, Virology Unit, Institut Pasteur of Madagascar, Antananarivo, Madagascar; OLHA HOLUBKA, affiliation L.V.Gromashevsky Institute of Epidemiology and Infectious Diseases National Academy of Medical Science of Ukraine, Kiev, Ukraine; Q. SUE HUANG, affiliation Institute of Environmental Science and Research, Wellington, New Zealand; HERVE A. KADJO, affiliation Respiratory Viruses Unit, Pasteur Institute of Côte d’Ivoire, Abidjan, Côte d’Ivoire; LYAZZAT KIYANBEKOVA, affiliation Zonal Virology Laboratory, Astana Center of Sanitary Epidemiology Expertise, Astana, Kazakhstan; HERMAN KOSASIH, affiliation US Naval Medical Research Unit No. 2, Jakarta, Indonesia; GABRIELA KUSZNIERZ, affiliation Instituto Nacional de Enfermedades Respiratorias “Dr. Emilio Coni,” Santa Fe, Argentina; JENNY LARA, affiliation National Influenza Center, Ministry of Health, San José, Costa Rica, MING LI, affiliation Division of Infectious Disease, Key Laboratory of Surveillance and Early-warning on Infectious Disease, Chinese Center for Disease Control and Prevention, Beijing, China; LIZA LOPEZ, affiliation Institute of Environmental Science and Research, Wellington, New Zealand; PHUONG VU MAI HOANG, affiliation National Institute of Hygiene and Epidemiology, Hanoi, Vietnam; CLÁUDIO MAIEROVITCH PESSANHA HENRIQUES, affiliation Ministry of Health, Brasília, DF, Brazil; MARIA LUISA MATUTE, affiliation national influenza center, ministry of health, tegucigalpa, honduras; alla mironenko, affiliation L.V.Gromashevsky Institute of Epidemiology and Infectious Diseases National Academy of Medical Science of Ukraine, Kiev, Ukrain; BRECHLA MORENO, affiliation National Influenza Center, IC Gorgas, Panama City, Panama; JOSHUA A. MOTT, affiliation US Centers for Disease Control and Prevention, Nairobi, Kenya; RICHARD NJOUOM; affiliation Service de Virologie, Centre Pasteur du Cameroun, Yaounde, Cameroon; NURHAYATI, affiliation US Naval Medical Research Unit No. 2, Jakarta, Indonesia; AKERKE OSPANOVA, affiliation Zonal Virology Laboratory, Astana Center of Sanitary Epidemiology Expertise, Astana, Kazakhstan; RHONDA OWEN, affiliation Vaccine Preventable Diseases Surveillance Section, Health Policy Protection Branch, Office of Health Protection, Department of Health, Woden, Australia; RICHARD PEBODY; affiliation Respiratory Diseases Department, Public Health England, Colindale, United Kingdom; KATE PENNINGTON, affiliation Vaccine Preventable Diseases Surveillance Section, Health Policy Protection Branch, Office of Health Protection, Department of Health, Woden, Australia; SIMONA PUZELLI, affiliation National Influenza Center, National Institute of Health, Rome, Italy; MAI THI QUYNH LE, affiliation National Institute of Hygiene and Epidemiology, Hanoi, Vietnam; NOROSOA HARLINE RAZANAJATOVO, affiliation National Influenza Center, Virology Unit, Institut Pasteur of Madagascar, Antananarivo, Madagascar; ANA RODRIGUES, affiliation National Institute of Health, Epidemiology Department, Lisbon, Portugal; JUAN MANUEL RUDI, affiliation Instituto Nacional de Enfermedades Respiratorias “Dr. Emilio Coni,” Santa Fe, Argentina; RAYMOND TZER PIN LIN, affiliation Communicable Diseases Division, Ministry of Health, Singapore, Singapore; MARIETJIE VENTER, affiliations Global Disease Detection, US-CDC, Pretoria, South Africa, Zoonoses Research Center, Department of Medical Virology, University of Pretoria, Pretoria, South Africa; MARIE-ASTRID VERNET, affiliation Service de Virologie, Centre Pasteur du Cameroun, Yaounde, Cameroon; SONAM WANGCHUK, affiliation Public Health Laboratory, Department of Public Health, Ministry of Health, Thimphu, Bhutan; JUAN YANG, affiliation Division of Infectious Disease, Key Laboratory of Surveillance and Early-warning on Infectious Disease, Chinese Center for Disease Control and Prevention, Beijing, China; HONGJIE YU, affiliation Division of Infectious Disease, Key Laboratory of Surveillance and Early-warning on Infectious Disease, Chinese Center for Disease Control and Prevention, Beijing, China; MARIA ZAMBON, affiliation Respiratory Virus Unit, Public Health England, Colindale, United Kingdom; FRANÇOIS SCHELLEVIS, affiliation Netherlands Institute for Health Services Research (NIVEL), Utrecht, The Netherlands; JOHN PAGET, affiliation Netherlands Institute for Health Services Research (NIVEL), Utrecht, The Netherlands; Global Influenza B Study.